Comparison of treatments for equine laryngeal hemiplegia using computational fluid dynamic analysis in an equine head model - Tucker, Michelle L.; Wilson, David G.; Bergstrom, Donald J.; Carmalt, James L. (Frontiers in Veterinary Science, 2024)
IntroductionComputational fluid dynamics (CFD) is gaining momentum as a useful mechanism for analyzing obstructive disorders and surgeries in humans and warrants further development for application in equine surgery. While advancements in procedures continue, much remains unknown about the specific impact that different surgeries have on obstructive airway disorders. The objective of this study was to apply CFD analysis to an equine head inhalation model replicating recurrent laryngeal neuropathy (RLN) and four surgical procedures. CFD was hypothesized to corroborate the order of the different trials based on impedance and to provide an impedance value numerically similar to the experimental results. In addition, it was hypothesized that CFD would offer insights into the changes in airflow associated with each procedure on a finite scale.MethodsAn equine cadaver head underwent airflow testing and computed tomographic (CT) scans to replicate the disease state (RLN) and four surgical procedures: laryngoplasty, combined laryngoplasty and corniculectomy, corniculectomy, and partial arytenoidectomy. Pressure measurements at the pharynx and trachea were recorded, along with airflow data, for each trial.Results and discussionThe CFD and experimental models showed that partial arytenoidectomy had the lowest impedance in this case. While this procedure did have the largest rima glottidis area, the remaining procedural order was not dictated by the rima glottidis area. Recurrent laryngeal neuropathy and combined laryngoplasty with corniculectomy models showed negative pressure concentration on the luminal surface of the left arytenoid cartilage, which indicated a greater collapsing force on the tissue in this region. Narrowing within the caudal larynx at the level of the saccule showed increased negative pressure and higher velocity in the procedures with greater impedance, while partial arytenoidectomy exhibited more uniform pressure and velocity. Although this specific experimental head model contradicted previous flow studies, the CFD model reflected the experimental findings for the procedure with the least impedance and provided some insights into why these discrepancies occurred in this particular case.